Cideb controls sterol‐regulated ER export of SREBP/SCAP by promoting cargo loading at ER exit sites. (12th March 2019) - Su, Lu; Zhou, Linkang; Chen, Feng‐Jung; Wang, Huimin; Qian, Hui; Sheng, Yuanyuan; Zhu, Yuangang; Yu, Hua; Gong, Xinqi; Cai, Li'e; Yang, Xuerui; Xu, Li; et al.
Abstract: SREBPs are master regulators of lipid homeostasis and undergo sterol‐regulated export from ER to Golgi apparatus for processing and activation via COPII‐coated vesicles. While COPII recognizes SREBP through its escort protein SCAP, factor(s) specifically promoting SREBP/SCAP loading to the COPII machinery remains unknown. Here, we show that the ER/lipid droplet‐associated protein Cideb selectively promotes the loading of SREBP/SCAP into COPII vesicles. Sterol deprivation releases SCAP from Insig and enhances ER export of SREBP/SCAP by inducing SCAP‐Cideb interaction, thereby modulating sterol sensitivity. Moreover, Cideb binds to the guanine nucleotide exchange factor Sec12 to enrich SCAP/SREBP at ER exit sites, where assembling of COPII complex initiates. Loss of Cideb inhibits the cargo loading of SREBP/SCAP, reduces SREBP activation, and alleviates diet‐induced hepatic steatosis. Our data point to a linchpin role of Cideb in regulated ER export of SREBP and lipid homeostasis. Synopsis: Factors that mediate sterol‐regulated targeting of SREBP/SCAP to COPII vesicles for lipid homeostasis are unknown. Cideb is an ER/lipid droplet‐localized protein that binds escort factor SCAP and SAR21 GTPase to promote ER‐to‐Golgi transport of SREBBP/SCAP on COPII vesicles. Cideb deficiency abrogates COPII‐mediated SREBP activation in mouse liver. Sterol‐controlled Cideb/SCAP interaction regulates SREBP processing and sterol sensitivity. Cideb transfers SCAP/SREBP to the active budding machinery by interacting with Sec12. Loss of Cideb inhibits the cargo loading of SREBP/SCAP, reduces SREBP activation, and protects mice from diet‐induced non‐alcoholic fatty liver disease. Abstract : The ER/lipid droplet‐localized protein Cideb binds escort factor SCAP and SAR21 GTPase to promote ER‐to‐Golgi transport of SREBP/SCAP on COPII vesicles.